1978
DOI: 10.1002/bit.260200905
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of glucose isomerase to ion‐exchange materials

Abstract: SummaryGlucose isomerase (D-XylOSe ketol-isomerase EC 5.3. I . 5 ) from Bacillus coagu~ans was partially purified and immobilized by adsorption to anion exchangers. The highest activities were obtained when the enzyme was adsorbed to DEAE-cellulose. On immobilization to DEAE-cellulose the measured optimum pH value for enzyme activity shifted from 7.2 to 6.8. There was no appreciable difference between the heat stabilities of soluble and immobilized enzyme. The K , Bpp values for the immobilized enzyme were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Furthermore, the specific activities of the immobilized chloroplasts were higher than those of the free chloroplasts (table 1). This increase of the specific activity was similar to the observation with glucoamylase [7] and glucose isomerase [8] immobilized on DEAE-cellulose. However, it may be asked whether the higher activity observed in our immobilized chloroplasts was mainly caused by uncoupling of photophosphorylation.…”
Section: Preparation Of Immobilized Chloroplastssupporting
confidence: 67%
See 3 more Smart Citations
“…Furthermore, the specific activities of the immobilized chloroplasts were higher than those of the free chloroplasts (table 1). This increase of the specific activity was similar to the observation with glucoamylase [7] and glucose isomerase [8] immobilized on DEAE-cellulose. However, it may be asked whether the higher activity observed in our immobilized chloroplasts was mainly caused by uncoupling of photophosphorylation.…”
Section: Preparation Of Immobilized Chloroplastssupporting
confidence: 67%
“…Thus, we have found no improvement in thermal stability upon adsorption to DEAE-cellulose in contrast with the chloroplasts entraped within polyacrylamide gel [l] or within microcapsules [3]. A similar observation has been made with glucose isomerase immobilized on DEAE-cellulose [8]. Figure 4 illustrates the continuous photoreduction of DCIP catalyzed by immobilized chloroplasts with water as the electron donor.…”
Section: Effect Of Temperaturementioning
confidence: 64%
See 2 more Smart Citations
“…Experiments that typically identify diffusion-limitation problems, such as comparisons of the Arrhenius and Lineweaver~Burk plots for free versus immobilized enzymes, or measurement of reaction rates for the enzyme bound to support" of varying pore or particle sizes, have concluded that no appreciable diffusion limitation exists (S6ret:lsen and Emborg, 1989;Schafhauser and Storey, 1992b). Similarly, experiments conducted to assess the presence of external mass-transfer limitations, such as increasing the agitation speed of the bioreaclor, had minimal effect on the apparent kinetic properties of the immobilized glucose isomerase and, therefore, showed no restrictions on the catalytic efficiency of the immobilized enzyme (Huitron and Limon-Lason, 1978;Schatbauser and Storey, 1992b). However, Y.Y.…”
Section: Inulinasementioning
confidence: 94%